1995
DOI: 10.1007/bf02515768
|View full text |Cite
|
Sign up to set email alerts
|

Factors and consequences of a non‐functional alary polymorphism in Pyrrhocoris apterus (Heteroptera: Pyrrhocoridae)

Abstract: Functional alary polymorphisms have been studied rather extensively in several insect species. This review article deals with factors controlling wing polymorphism in a flightless species, Pyrrhocoris apterus (L.), and discusses its adaptive significance and mechanisms for their persistence under natural conditions. The macropterous morph is determined by a recessive allele whose penetrance depends on photoperiod and temperature. Natural populations of this species contain a small fraction of flightless macrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…While we infer that there is evidence for a genetic component to the differentiation of wing morphotypes, there may also be an environmental component to this differentiation. In other species of insects, the penetrance of genetic factors regulating wing development can be mediated by environmental factors, and therefore the expression of phenotype can be highly complex 71,72 . The differing patterns of wing loss in the different clades of Z. fenestrata Clade 1 may indicate the interactive roles played between the environment and genetics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While we infer that there is evidence for a genetic component to the differentiation of wing morphotypes, there may also be an environmental component to this differentiation. In other species of insects, the penetrance of genetic factors regulating wing development can be mediated by environmental factors, and therefore the expression of phenotype can be highly complex 71,72 . The differing patterns of wing loss in the different clades of Z. fenestrata Clade 1 may indicate the interactive roles played between the environment and genetics.…”
Section: Discussionmentioning
confidence: 99%
“…Other environmental factors that can influence wing development include abiotic factors such as temperature 65 and photoperiod 69 as well as biotic factors such as food resources 65 and population density 70 . Many of these environmental regulators of wing development also have a genetic component, for instance the fully winged morphotype of the red fire bug (Pyrrhocoris apterus) is determined by a recessive allele, whose penetrance depends on photoperiod and temperature 71 . Environmentally induced wing polyphenism in insects can also be transgenerational, with the level of the hormone ecdysone in the mother (regulated by population density) altering the expression of wing development in the offspring of the pea aphid (Acyrthosiphon pisum) 72 .…”
Section: Introductionmentioning
confidence: 99%
“…Environmental factors, such as photoperiod (Harada 1993(Harada , 1998Honĕk 1979;Saulich 1996, Socha 2001), food quality (Solbreck 1986), high population density (Kim and McPheron 1993), etc. or genetics (Honĕk 1995, Solbreck 1986) influence wing development. Velidia berytoides Uhler, 1894:207;Bergroth, 1914:116;Costa-Lima, 1927:541;Maldonado-Capriles and Navarro, 1967:49;Woodruff et al, 1998: 93.…”
Section: Systematic Entomologymentioning
confidence: 99%
“…As the distinct phenotypes of wing-dimorphic species have very similar genetic backgrounds, such taxa present ideal systems for exploring the molecular basis of wing loss. Previous studies of wing-dimorphic species have suggested that wing polymorphism can be genetically determined [23][24][25][26][27], controlled by environmentally driven gene expression (polyphenism; [11,[28][29][30]), include both genetic and environmental components [31], or be under the control of epigenetic factors [32,33].…”
Section: Introductionmentioning
confidence: 99%